Plasma levels of glucagon‐like peptide 1 and markers of obesity among young and healthy adults. (27th April 2015) - van der Stouwe, Jan Gerrit; Aeschbacher, Stefanie; Krisai, Philipp; Schoen, Tobias; Meyre, Pascal; Todd, John; Estis, Joel; Risch, Martin; Risch, Lorenz; Conen, David
Summary Objective Glucagon‐like peptide 1 (GLP‐1)‐related pathways may partially explain the strong relationship between obesity and type 2 diabetes. We therefore aimed to evaluate the relationships between fasting GLP‐1 levels, body fat mass and other obesity markers in a large sample of young and healthy adults. Design and Patients Our population‐based study included 2096 individuals aged 24–44. Exclusion criteria were prevalent cardiovascular disease, diabetes or a body mass index (BMI) >35 kg/m2. Body fat mass was obtained by bioelectrical impedance analysis. Multivariable linear regression models were constructed to assess the relationships of GLP‐1 with various measures of body composition. Results Median age of our population was 37 years, median BMI 24·1 kg/m2 and median body fat 25·1%. A strong positive correlation was observed in age‐adjusted models between GLP‐1 and fat mass in men (β (95% confidence interval) 1·38 (0·69; 2·07), P < 0·001) and women (1·27 (0·65; 1·89), P < 0·001) as well as fully adjusted models including BMI in men [0·87 (0·27; 1·46), P < 0·01] but not women [0·29 (−0·07; 0·64), P = 0·11]. The relationships of GLP‐1 with BMI for men and women [0·00 (−0·34; 0·34), P = 0·99] [−0·02 (−0·28; 0·25), P = 0·91] and waist circumference [0·43 (−0·45; 1·30), P = 0·34] [0·37 (−0·44; 1·18), P = 0·37], respectively, were not significant after multivariable adjustment including fat mass. Conclusion Among young and healthy adults, GLP‐1 levels are strongly and independently related to body fat mass especially in men but not BMI or waist circumference. These results raise the hypothesis that GLP‐1 may be implicated in body fat mass regulation.